2009
DOI: 10.3324/haematol.2009.008524
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged ex vivo culture of human bone marrow mesenchymal stem cells influences their supportive activity toward NOD/SCID-repopulating cells and committed progenitor cells of B lymphoid and myeloid lineages

Abstract: The online version of this article has a supplementary appendix. BackgroundBone marrow mesenchymal stem cells support proliferation and differentiation of hematopoietic progenitor cells in vitro. Since these cells constitute a rare subset of bone marrow cells, mesenchymal stem cell preparations for clinical purposes require a preparative step of ex vivo multiplication. The aim of our study was to analyze the influence of culture duration on mesenchymal stem cell supportive activity. Design and MethodsMesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 26 publications
1
52
0
1
Order By: Relevance
“…MSCs have previously demonstrated their capacity to facilitate regeneration and regulate immune responses in a range of animal models; however, major factors related to life span and tumorigenicity limit their widespread use in a clinical setting [28][29][30][31][32]. Recent reports have described MSC-like cells derived from iPSCs [33][34][35] with a greater proliferative capacity, lower immunogenicity, and greater immunoregulatory function compared with primary MSC cultures [33,43,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs have previously demonstrated their capacity to facilitate regeneration and regulate immune responses in a range of animal models; however, major factors related to life span and tumorigenicity limit their widespread use in a clinical setting [28][29][30][31][32]. Recent reports have described MSC-like cells derived from iPSCs [33][34][35] with a greater proliferative capacity, lower immunogenicity, and greater immunoregulatory function compared with primary MSC cultures [33,43,45].…”
Section: Discussionmentioning
confidence: 99%
“…Successive passages slow the proliferation rate, and MSCs progressively lose their multipotency and lack immunosuppressive activity. In addition, aging and age-related disorders significantly impair the survival and differentiation potential of BM-MSCs, thus limiting their therapeutic efficacy [28][29][30][31][32]. Therefore, it is important to identify alternative sources of MSCs before they can be used as a mainstream treatment for organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, IL-6 was identified to mediate human BMMSCs' contribution to in vitro differentiation of hematopoietic progenitor cells toward myeloid and lymphoid cells [35]. Xie et al reported that IL-6 enhanced retinoic acid-induced granulocytic differentiation of APL cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, we ruled out the possibility of participation of G-CSF and PGE2 in UC-MSCs' differentiation induction. Recently, IL-6 was identified to mediate human bone marrow MSCs' (BMMSCs) contribution to in vitro differentiation of hematopoietic progenitor cells toward myeloid and lymphoid cells [35]. Xie et al reported that IL-6 dramatically enhanced retinoic acid-induced granulocytic differentiation of HL-60 cells (a leukemic cell line derived from M2) [49].…”
Section: Il-6 Is the Major Soluble Mediator Of The Differentiation Inmentioning
confidence: 99%
See 1 more Smart Citation